Serviceability limit checks on reinforced concrete beams according to CP 110 and yield-line analysis of slabs / [mikrofilem] - 416070 Mohamad Kahari Ambran
Thesis (Bachelor of Civil Engineering) - Universiti Teknologi Malaysia, 1978